Hypokalemic periodic paralysis: a case report - Kibe, Rutuja; Biniwale, Nishit; Biniwale, Atul (International Journal of Research in Medical Sciences, 2017)
Hypokalemic periodic paralysis (HPP), a clinical syndrome characterized by low serum potassium, is a rare but treatable cause of acute muscular weakness. The etiology can be attributed to various factors and can be either idiopathic or due to secondary causes. The approach to a case of HPP involves identifying the underlying etiology and prompt replenishment and maintenance of the potassium levels. Further management depends on the cause, frequency of attacks, severity of symptoms and the duration of the illness.